Konsep Pendidikan Akhlak Perspektif Umar Ibnu Ahmad Barjah di dalam Kitab Akhlakul Lil Banin Jilid I - Zahara, Fatimah Nurul; Satria, Rengga (ANWARUL, 2024)
Morality and character education play a crucial role in shaping an individual's character, guiding actions in various life contexts. Kitab Akhlaqul Lil Banin Jilid 1, with a long history in Islamic education, serves as a primary guide in shaping the morals, ethics, and behavior of children according to Islamic principles. This research aims to describe the concept of students' morality according to this book and identify the emphasized moral values. The applied research method is qualitative, specifically library research. The research findings indicate that Kitab Al-Akhlak Lil Banin provides a comprehensive guide to the moral education of boys. In this book, children are taught moral values, courtesy, honesty, and obedience to Allah. Through 33 chapters, the book discusses various aspects of Islamic ethics and morals specifically directed at boys. By exploring Islamic moral principles in the context of home, school, and society, it is expected that children can understand and internalize Islamic morals and ethics in their daily lives.